Effects of exercise sequence and velocity loss threshold during resistance training on following endurance and strength performance during concurrent training - Najera-Ferrer, P.; Perez-Caballero, C.; Gonzales-Badillo, J. J.; Pareja Blanco, F. (International Journal of Sports Physiology and Performance, 2021)
Purpose: This study aimed to analyze the response to 4 concurrent training interventions differing in the training sequence and in the velocity loss (VL) threshold during strength training (20% vs 40%) on following endurance and strength performance.